Pengaruh Kompetensi Pedagogik Guru terhadap Kemampuan Literasi Peserta Didik pada Mata Pelajaran Pendidikan Pancasila dan Kewarganegaraan - Indriani, Dewi; Jamaludin, Ujang; Bahrudin, Febrian Alwan (Jurnal Kependidikan Media, 2024)
The aim of this research was to determine the effect of teachers pedagogical competence on students literacy skills in Pancasila and Civics Education subjects. The research took place at SMA Negeri 5 Kota Serang in 2023, with the study population being eleventh-grade students during the academic year 2022/2023, and uses a quantitative approach with correlational descriptive statistical analysis techniques. The probability sampling technique with the type of proportionate stratified random sampling was used for sampling. To obtain data, a questionnaire was used. The results showed that variable X on variable Y has a level of influence based on a significance value of (0.001 ≤ 0.05) and based on the t value: it is known that the t count value = 33.936 and the t table value = 2.028 (33.936 ≥ 2.028). Thus, it can be concluded that the pedagogical competence of teachers effects the literacy skills of students in Pancasila and Civics Education subjects with an influence level of 97.0%.